Optical glass, optical element and optical instrument
By optimizing the component design of optical glass, including SiO2, ZrO2, BaO, CaO, TiO2 and ZnO, the problem of high cost of optical glass raw materials is solved, and optical glass with low density and excellent performance is achieved to meet lightweight optical instruments demand.
Patent Information
- Application Number
- CN202310696544.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
AI Technical Summary
The raw materials of existing optical glass are costly and it is difficult to meet the needs of lightweight optical instruments.
通过优化光学玻璃的组分设计,含有SiO2、ZrO2、BaO、CaO、TiO2和ZnO等成分,控制其折射率和阿贝数,确保密度低于4.00 g/cm3,并在合理的成本下满足光学性能要求。
It realizes optical glass with low raw material cost and low density, meets the use needs of lightweight optical instruments and improves the market competitiveness of the products.
Smart Images

Figure BDA0004281954210000121 
Figure BDA0004281954210000151 
Figure BDA0004281954210000161
Abstract
Description
Technical Field
[0001] The invention relates to optical glass, in particular to optical glass with low density, and optical elements and optical instruments made of the same. Background Art
[0002] In recent years, optical camera equipment, especially small optical camera equipment, such as digital cameras, camera phones, surveillance cameras, driving recorders, etc., has been widely used. These optical camera equipment have two main development trends: first, the size of the camera equipment is getting smaller and smaller, which can be easily coupled with other equipment; second, the imaging quality is getting higher and higher, which can meet the needs of high-definition video applications. As instruments using optical systems develop towards digitalization and high precision, the requirements for lightweight optical components such as lenses used in various optical instruments are getting higher and higher, which requires the optical glass used to manufacture optical components to have a lower density.
[0003] The market competition of optical glass is becoming increasingly fierce. Only products with low raw material cost and excellent comprehensive performance have stronger competitiveness. Chinese patent CN1198414A discloses an optical glass with a refractive index of 1.65-1.80 and an Abbe number of 28-42, which contains 31-50% Nb2O5, which greatly increases the raw material cost of optical glass and is not conducive to improving the market competitiveness of products. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an optical glass with low raw material cost and low density.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] (1) Optical glass, the components of which, expressed in percentage by weight, contain: SiO2: 25-35%; ZrO2: 1-8%; BaO: 30-40%; CaO: 1-9%; TiO2: 6-16%; ZnO: 1-9%, wherein (SiO2+ZnO) / (BaO+TiO2) is 0.48-1.0.
[0007] (2) The optical glass according to (1), wherein the components, expressed in weight percentage, further contain: B2O3: 0-9%; and / or Al2O3: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-5%; and / or Li2O: 0-5%; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or WO3: 0-5%; and / or Nb2O5: 0-5%; and / or Ln2O3: 0-10%; and / or a clarifier: 0-1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0008] (3) Optical glass, comprising SiO2, ZrO2, BaO, CaO, TiO2 and ZnO, wherein the composition is expressed in weight percentage, wherein (SiO2+ZnO) / (BaO+TiO2) is 0.48 to 1.0, and the refractive index of the optical glass is n d is 1.69~1.75, Abbe number v d 34.5~40.5, density ρ is 4.00g / cm 3 the following.
[0009] (4) The optical glass according to (3), wherein the components, expressed in weight percentage, are: SiO2: 25-35%; and / or ZrO2: 1-8%; and / or BaO: 30-40%; and / or CaO: 1-9%; and / or TiO2: 6-16%; and / or ZnO: 1-9%; and / or B2O3: 0-9%; and / or Al2O3: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-5%; and / or Li2O: 0-5%; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or WO3: 0-5%; and / or Nb2O5: 0-5%; and / or Ln2O3: 0-10%; and / or clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0010] (5) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: TiO2 / (CaO+Al2O3) is 0.5 to 6.0, preferably TiO2 / (CaO+Al2O3) is 0.6 to 5.0, more preferably TiO2 / (CaO+Al2O3) is 0.8 to 3.0, and further preferably TiO2 / (CaO+Al2O3) is 1.0 to 2.0; and / or BaO / (ZrO2+TiO2) is 1.4 to 5.0, preferably BaO / (ZrO2+TiO2) is 1.5 to 3.5, more preferably BaO / (ZrO2+TiO2) is 1.6 to 3.0, and further preferably BaO / (ZrO2+TiO2) is 1.8 to 2.8; and / or (SiO2+ZnO) / (BaO+TiO2) is 0.5 to 0. 91, preferably (SiO2+ZnO) / (BaO+TiO2) is 0.6-0.9, more preferably (SiO2+ZnO) / (BaO+TiO2) is 0.65-0.85; and / or (SiO2+ZrO2) / ZnO is 4.0-15.0, preferably (SiO2+ZrO2) / ZnO is 5.0-12.0, more preferably (SiO2+ZrO2) / ZnO is 6.0~10.0, more preferably (SiO2+ZrO2) / ZnO is 6.0~9.5; and / or (TiO2+ZnO) / CaO is 1.0~10.0, preferably (TiO2+ZnO) / CaO is 1.5~8.0, more preferably (TiO2+ZnO) / CaO is 2.0~5.0, further preferably (TiO2+ZnO) / CaO is 2.5~4.5.
[0011] (6) The optical glass according to any one of (1) to (4), wherein the composition is expressed in weight percentage, wherein: (CaO + SrO) / ZnO is 0.3 to 5.0, preferably (CaO + SrO) / ZnO is 0.5 to 3.0, more preferably (CaO + SrO) / ZnO is 0.6 to 2.0, and further preferably (CaO + SrO) / ZnO is 0.8 to 1.5; and / or TiO2 / (ZnO + Li2O + SrO) is 0.7 or more, preferably TiO2 / (ZnO + Li2O + SrO) is 0.9 to 10.0, More preferably, TiO2 / (ZnO+Li2O+SrO) is 1.0 to 5.0, and further preferably, TiO2 / (ZnO+Li2O+SrO) is 1.5 to 3.5; and / or SiO2 / (BaO+ZnO+Li2O) is 0.5 to 1.0, and preferably, SiO2 / (BaO+ZnO+Li2O) is 0.6 to 0.95, and more preferably, SiO2 / (BaO+ZnO+Li2O) is 0.65 to 0.95, and further preferably, SiO2 / (BaO+ZnO+Li2O) is 0.7 to 0.9; and / or
[0012] (Li2O+Na2O+K2O) / ZrO2 is 0.7 or less, preferably (Li2O+Na2O+K2O) / ZrO2 is 0.5 or less, more preferably (Li2O+Na2O+K2O) / ZrO2 is 0.4 or less, and further preferably (Li2O+Na2O+K2O) / ZrO2 is 0.01 to 0.3; and / or Ln2O3 / TiO2 is 0.4 or less, preferably Ln2O3 / TiO2 is 0.3 or less, and more preferably Ln2O3 / TiO2 is 0.2 or less, It is further preferred that Ln2O3 / TiO2 is less than 0.1; and / or (B2O3+Ln2O3) / ZrO2 is less than 5.0, preferably (B2O3+Ln2O3) / ZrO2 is 0.1-3.0, more preferably (B2O3+Ln2O3) / ZrO2 is 0.3-2.0, further preferably (B2O3+Ln2O3) / ZrO2 is 0.5-1.5, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
[0013] (7) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: SiO2: 27-33%, preferably SiO2: 28-32%; and / or Al2O3: 1-6%, preferably Al2O3: 2-5%; and / or ZrO2: 2-7%, preferably ZrO2: 3-6%; and / or BaO: 32-38%, preferably BaO: 34-37%; and / or CaO: 3-8%, preferably CaO: 4-6%; and / or SrO: 0-2%, preferably SrO: 0-1%; and / or TiO2: 9-15%, preferably TiO2: 10-13%; and / or ZnO: 3-8%, preferably ZnO: 4-6%; and / or Na2O: 0-3%, preferably Na2O: 0-2%; and / or B2 O3: 2-7%, preferably B2O3: 3-6%; and / or MgO: 0-2%, preferably MgO: 0-1%; and / or Li2O: 0-2%, preferably Li2O: 0-1%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%; and / or Ln2O3: 0-5%, preferably Ln2O3: 0-2%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0014] (8) The optical glass according to any one of (1) to (4), wherein its components do not contain MgO; and / or do not contain SrO; and / or do not contain Li2O; and / or do not contain K2O; and / or do not contain WO3; and / or do not contain Nb2O5; and / or do not contain SnO2; and / or do not contain SnO; and / or do not contain CeO2; and / or do not contain As2O3; and / or do not contain PbO; and / or do not contain Ln2O3, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
[0015] (9) The refractive index n of the optical glass according to any one of (1) to (4) d is 1.69 to 1.75, preferably 1.70 to 1.74, more preferably 1.715 to 1.73, and the Abbe number v d It is 34.5-40.5, preferably 35-40, and more preferably 36-39.
[0016] (10) The optical glass according to any one of (1) to (4) has a density of 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.80g / cm 3 Below; and / or thermal expansion coefficient α 100 / 300℃ 94×10 -7 / K or less, preferably 92×10 -7 / K or less, more preferably 88×10 -7 / K or less; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A The weather resistance CR is 2 or more, preferably 1; and / or the air bubble degree is A or more, preferably A0 or more, more preferably A 00 level; and / or transition temperature T g is 700°C or less, preferably 690°C or less, more preferably 685°C or less; and / or the striae is C or above, preferably B or above; and / or the viscosity at 1400°C is 45 poise or less, preferably 35 poise or less, more preferably 1 to 25 poise; and / or the light transmittance τ 400nm It is 85.0% or more, preferably 87.0% or more, more preferably 88.0% or more, and further preferably 89.0% or more.
[0017] (11) A glass preform made of the optical glass described in any one of (1) to (10).
[0018] (12) An optical element, made of the optical glass described in any one of (1) to (10), or made of the glass preform described in (11).
[0019] (13) An optical instrument comprising the optical glass described in any one of (1) to (10) and / or the optical element described in (12).
[0020] The beneficial effects of the present invention are as follows: through reasonable component design, the optical glass raw material of the present invention has low cost and low density, which meets the requirements for the use of lightweight optical instruments. DETAILED DESCRIPTION
[0021] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.
[0022] [Optical glass]
[0023] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0024] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0025] <Essential Components and Optional Components>
[0026] SiO2 is the skeleton of optical glass. As a glass network generator, it has the function of maintaining the chemical stability of glass and improving the resistance of glass to devitrification. In the present invention, the above effect is obtained by containing more than 25% SiO2. Preferably, the content of SiO2 is more than 27%, and more preferably, the content of SiO2 is more than 28%. If the content of SiO2 is higher than 35%, the glass meltability is reduced, vitrification is difficult, and it is easy to form stones and other internal quality problems. At the same time, the transition temperature of the glass rises, and too high a melting temperature will also cause the light transmittance of the glass to deteriorate. Therefore, the upper limit of the content of SiO2 is 35%, preferably 33%, and more preferably 32%.
[0027] B2O3 can improve the melting property and resistance to devitrification of glass, but when its content is too high, the chemical stability of glass decreases and the thermal expansion coefficient is adversely affected. Therefore, the content of B2O3 in the present invention is 0-9%, preferably 2-7%, and more preferably 3-6%.
[0028] Al2O3 can improve the chemical stability of glass, and increase the mechanical strength and weather resistance of glass, but when its content is too high, the meltability of glass decreases and the anti-crystallization performance deteriorates. Therefore, the content of Al2O3 is 0-8%, preferably 1-6%, and more preferably 2-5%.
[0029] ZrO2 can improve the hardness, refractive index and chemical stability of optical glass, reduce the thermal expansion coefficient of glass, and optimize high-temperature viscosity. When the content of ZrO2 is too high, the resistance to devitrification of glass decreases, the difficulty of melting increases, the melting temperature rises, and inclusions appear inside the glass and the light transmittance decreases. Therefore, the content of ZrO2 in the present invention is 1 to 8%, preferably 2 to 7%, and more preferably 3 to 6%.
[0030] BaO can increase the refractive index of glass, improve the thermal expansion coefficient and high temperature viscosity of glass, but if its content is too high, the chemical stability of glass will be deteriorated. Therefore, the content of BaO is limited to 30-40%, preferably 32-38%, and more preferably 34-37%.
[0031] CaO helps to improve the refractive index and hardness of glass and optimize the abrasiveness of glass, but if the content of CaO is too high, the anti-devitrification performance of glass will decrease. Therefore, the content of CaO is 1-9%, preferably 3-8%, and more preferably 4-6%.
[0032] SrO can adjust the refractive index and Abbe number of glass, but if its content is too high, the chemical stability of glass will be reduced, and the cost of glass will also rise rapidly. Therefore, the content of SrO is limited to 0-5%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that SrO is not contained.
[0033] MgO can reduce the relative partial dispersion of glass, but when the MgO content is too high, the refractive index of the glass is difficult to meet the design requirements, and the anti-crystallization performance and stability of the glass are reduced. Therefore, the MgO content is limited to 0-5%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that MgO is not contained.
[0034] TiO2 has the effect of increasing the refractive index and dispersion of glass. A proper amount of TiO2 can make the glass more stable and reduce the viscosity of the glass. If the content of TiO2 is too high, the crystallization tendency of the glass increases and the transition temperature rises. Therefore, the content of TiO2 in the present invention is 6 to 16%, preferably 9 to 15%, and more preferably 10 to 13%.
[0035] In some embodiments, controlling the ratio of TiO2 / (CaO+Al2O3) between the content of TiO2 and the total content of CaO and Al2O3 (CaO+Al2O3) in the range of 0.5 to 6.0 is beneficial to reducing the density of the glass and preventing the deterioration of the anti-crystallization performance of the glass. Therefore, preferably TiO2 / (CaO+Al2O3) is 0.5 to 6.0, and more preferably TiO2 / (CaO+Al2O3) is 0.6 to 5.0. Furthermore, controlling TiO2 / (CaO+Al2O3) in the range of 0.8 to 3.0 can also optimize the striation degree of the glass. Therefore, it is further preferred that TiO2 / (CaO+Al2O3) is 0.8 to 3.0, and it is further preferred that TiO2 / (CaO+Al2O3) is 1.0 to 2.0.
[0036] In some embodiments, the ratio of the content of BaO to the total content of ZrO2 and TiO2 ZrO2+TiO2 BaO / (ZrO2+TiO2) is controlled within the range of 1.4 to 5.0, which can increase the hardness of the glass and reduce the transition temperature and thermal expansion coefficient of the glass. Therefore, preferably BaO / (ZrO2+TiO2) is 1.4 to 5.0, more preferably BaO / (ZrO2+TiO2) is 1.5 to 3.5, further preferably BaO / (ZrO2+TiO2) is 1.6 to 3.0, and further preferably BaO / (ZrO2+TiO2) is 1.8 to 2.8.
[0037] ZnO can adjust the refractive index and dispersion of glass, reduce the transition temperature of glass, and allow glass to be melted at a lower temperature, thereby increasing the light transmittance of glass. If the ZnO content is too high, the high-temperature viscosity of the glass will increase, the difficulty of glass molding will increase, and the anti-crystallization performance will deteriorate. Therefore, the ZnO content is 1-9%, preferably 3-8%, and more preferably 4-6%.
[0038] In some embodiments, the ratio (CaO+SrO) / ZnO between the total content of CaO and SrO CaO+SrO and the content of ZnO is controlled within the range of 0.3 to 5.0, which can optimize the light transmittance and high temperature viscosity of the glass and prevent the thermal expansion coefficient of the glass from increasing. Therefore, preferably (CaO+SrO) / ZnO is 0.3 to 5.0, more preferably (CaO+SrO) / ZnO is 0.5 to 3.0, further preferably (CaO+SrO) / ZnO is 0.6 to 2.0, and further preferably (CaO+SrO) / ZnO is 0.8 to 1.5.
[0039] In some embodiments, the ratio (SiO2+ZnO) / (BaO+TiO2) between the total content of SiO2 and ZnO SiO2+ZnO and the total content of BaO and TiO2 BaO+TiO2 is controlled within the range of 0.48 to 1.0, which can prevent the density of the glass from increasing while optimizing the striation degree and high temperature viscosity of the glass. Therefore, it is preferred that (SiO2+ZnO) / (BaO+TiO2) is 0.48 to 1.0, more preferably (SiO2+ZnO) / (BaO+TiO2) is 0.5 to 0.91, further preferably (SiO2+ZnO) / (BaO+TiO2) is 0.6 to 0.9, and further preferably (SiO2+ZnO) / (BaO+TiO2) is 0.65 to 0.85.
[0040] In some embodiments, by controlling the ratio of the total content of SiO2 and ZrO2 SiO2 + ZrO2 to the content of ZnO (SiO2 + ZrO2) / ZnO in the range of 4.0 to 15.0, the light transmittance of the glass can be prevented from decreasing while reducing the thermal expansion coefficient of the glass. Therefore, it is preferred that (SiO2 + ZrO2) / ZnO is 4.0 to 15.0, and it is more preferred that (SiO2 + ZrO2) / ZnO is 5.0 to 12.0. Furthermore, by controlling (SiO2 + ZrO2) / ZnO in the range of 6.0 to 10.0, the high temperature viscosity of the glass can be further optimized. Therefore, it is further preferred that (SiO2 + ZrO2) / ZnO is 6.0 to 10.0, and it is further preferred that (SiO2 + ZrO2) / ZnO is 6.0 to 9.5.
[0041] In some embodiments, the ratio (TiO2+ZnO) / CaO between the total content of TiO2 and ZnO TiO2+ZnO and the content of CaO is controlled within the range of 1.0 to 10.0, which can improve the bubble degree and striae degree of the glass and prevent the weather resistance from deteriorating. Therefore, preferably (TiO2+ZnO) / CaO is 1.0 to 10.0, more preferably (TiO2+ZnO) / CaO is 1.5 to 8.0, further preferably (TiO2+ZnO) / CaO is 2.0 to 5.0, and further preferably (TiO2+ZnO) / CaO is 2.5 to 4.5.
[0042] Li2O can lower the transition temperature of glass, adjust the high temperature viscosity of glass, and improve the solubility of glass, but its high content is detrimental to the chemical stability and cost economy of glass. Therefore, the content of Li2O in the present invention is 5% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, it is further preferred that Li2O is not contained.
[0043] In some embodiments, the ratio of TiO2 / (ZnO+Li2O+SrO) between the content of TiO2 and the total content of ZnO, Li2O, and SrO ZnO+Li2O+SrO is controlled to be above 0.7, which can reduce the transition temperature of the glass and optimize the anti-crystallization performance of the glass. Therefore, it is preferred that TiO2 / (ZnO+Li2O+SrO) is above 0.7, and it is more preferred that TiO2 / (ZnO+Li2O+SrO) is 0.9 to 10.0. Furthermore, controlling TiO2 / (ZnO+Li2O+SrO) within the range of 1.0 to 5.0 can further optimize the bubble degree and weather resistance of the glass. Therefore, it is further preferred that TiO2 / (ZnO+Li2O+SrO) is 1.0 to 5.0, and it is further preferred that TiO2 / (ZnO+Li2O+SrO) is 1.5 to 3.5.
[0044] In some embodiments, the ratio of the content of SiO2 to the total content of BaO, ZnO, and Li2O, BaO+ZnO+Li2O, SiO2 / (BaO+ZnO+Li2O), is controlled within the range of 0.5 to 1.0, which can improve the chemical stability of the glass and optimize the abrasiveness of the glass. Therefore, preferably SiO2 / (BaO+ZnO+Li2O) is 0.5 to 1.0, and more preferably SiO2 / (BaO+ZnO+Li2O) is 0.6 to 0.95. Further, controlling SiO2 / (BaO+ZnO+Li2O) within the range of 0.65 to 0.95 can further optimize the bubble degree of the glass. Therefore, it is further preferred that SiO2 / (BaO+ZnO+Li2O) is 0.65 to 0.95, and it is further preferred that SiO2 / (BaO+ZnO+Li2O) is 0.7 to 0.9.
[0045] Na2O has the function of improving the fusibility of glass and can improve the melting effect of glass. If the content of Na2O is too high, the chemical stability and weather resistance of glass will be reduced. Therefore, the content of Na2O is 0-5%, preferably 0-3%, and more preferably 0-2%.
[0046] K2O has the effect of improving the thermal stability and melting property of glass, but if its content exceeds 5%, the devitrification resistance and chemical stability of glass deteriorate. Therefore, the content of K2O in the present invention is 0-5%, preferably 0-2%, more preferably 0-1%. In some embodiments, it is further preferred that K2O is not contained.
[0047] In some embodiments, controlling the ratio of the total content of Li2O, Na2O, and K2O, Li2O+Na2O+K2O, to the content of ZrO2, (Li2O+Na2O+K2O) / ZrO2, to be below 0.7 is beneficial for obtaining the desired optical constants and optimizing the high temperature viscosity and weather resistance of the glass. Therefore, preferably (Li2O+Na2O+K2O) / ZrO2 is below 0.7, more preferably (Li2O+Na2O+K2O) / ZrO2 is below 0.5, further preferably (Li2O+Na2O+K2O) / ZrO2 is below 0.4, and further preferably (Li2O+Na2O+K2O) / ZrO2 is 0.01 to 0.3.
[0048] Nb2O5 can increase the refractive index of glass, improve the chemical stability and resistance to devitrification of glass, but if its content is too high, the dispersion of glass will increase, and it will be difficult to obtain glass with target optical constants. At the same time, the cost and density of glass will increase, and the short-wave transmittance in the visible light region will decrease. Therefore, the content of Nb2O5 in the present invention is 5% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, it is further preferred that Nb2O5 is not contained.
[0049] WO3 can improve the refractive index and mechanical strength of glass. If the content of WO3 exceeds 5%, the thermal stability of glass decreases and the resistance to devitrification decreases. Therefore, the upper limit of WO3 content is 5%, preferably 2%, and more preferably 1%. In some embodiments, it is further preferred that WO3 is not contained.
[0050] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3) is a component that improves the refractive index and chemical stability of glass. By controlling the content of Ln2O3 to be less than 10%, the devitrification resistance of glass can be prevented from decreasing. Preferably, the upper limit of the Ln2O3 content range is 5%, and more preferably the upper limit is 2%. In some embodiments, it is further preferred that Ln2O3 is not contained.
[0051] In some embodiments, controlling Ln2O3 / TiO2 to be below 0.4 can prevent the weather resistance and chemical stability of the glass from being reduced and optimize the high temperature viscosity of the glass. Therefore, Ln2O3 / TiO2 is preferably below 0.4, more preferably below 0.3, further preferably below 0.2, and even more preferably below 0.1.
[0052] In some embodiments, the ratio (B2O3+Ln2O3) / ZrO2 between the total content of B2O3 and Ln2O3 B2O3+Ln2O3 and the content of ZrO2 is controlled to be below 5.0, which can prevent the chemical stability of the glass from deteriorating while lowering the transition temperature of the glass. Therefore, it is preferred that (B2O3+Ln2O3) / ZrO2 is below 5.0. Furthermore, by controlling (B2O3+Ln2O3) / ZrO2 within the range of 0.1 to 3.0, the bubble degree of the glass can be further optimized. Therefore, it is more preferred that (B2O3+Ln2O3) / ZrO2 is 0.1 to 3.0, further preferred that (B2O3+Ln2O3) / ZrO2 is 0.3 to 2.0, and further preferred that (B2O3+Ln2O3) / ZrO2 is 0.5 to 1.5.
[0053] In the present invention, by containing 0-1% of one or more components of Sb2O3, SnO, SnO2, and CeO2 as a clarifier, the clarification effect of the glass can be improved and the bubble degree of the glass can be improved. The content of the clarifier is preferably 0-0.5%, and the content of the clarifier is more preferably 0-0.2%. Sb2O3 is preferably used as a clarifier. When the content of Sb2O3 exceeds 1%, the clarification performance of the glass tends to decrease. At the same time, due to its strong oxidizing effect, it promotes the corrosion of the platinum or platinum alloy vessel for melting glass and the deterioration of the forming mold. Therefore, the content of Sb2O3 in the present invention is preferably 0-1%, more preferably 0-0.5%, and further preferably 0-0.2%. SnO and SnO2 can also be used as clarifiers, but when their content exceeds 1%, the tendency of the glass to color increases, or when the glass is heated, softened, and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency to devitrification. Therefore, the content of SnO2 in the present invention is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO2; the content of SnO is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO. The role and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain CeO2.
[0054] <Components that should not be contained>
[0055] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0056] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.
[0057] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.
[0058] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0059] Next, the properties of the optical glass of the present invention will be described.
[0060] <Refractive Index and Abbe Number>
[0061] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.
[0062] In some embodiments, the refractive index (n d ) has a lower limit of 1.69, a preferred lower limit of 1.70, and a more preferred lower limit of 1.715.
[0063] In some embodiments, the refractive index (n d ) has an upper limit of 1.75, a preferred upper limit of 1.74, and a more preferred upper limit of 1.73.
[0064] In some embodiments, the Abbe number (ν d ) has a lower limit of 34.5, a preferred lower limit of 35, and a more preferred lower limit of 36.
[0065] In some embodiments, the Abbe number (ν d ) has an upper limit of 40.5, a preferred upper limit of 40, and a more preferred upper limit of 39.
[0066] <density>
[0067] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.
[0068] In some embodiments, the density (ρ) of the optical glass of the present invention is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.80g / cm 3 the following.
[0069] <Coefficient of Thermal Expansion>
[0070] Thermal expansion coefficient of optical glass (α 100 / 300℃ ) The data at 100-300℃ were tested according to the method specified in GB / T7962.16-2010.
[0071] In some embodiments, the thermal expansion coefficient (α 100 / 300℃ ) is 94×10 -7 / K or less, preferably 92×10 -7 / K or less, more preferably 88×10 -7 / K or less.
[0072] <Water resistance stability>
[0073] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0074] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.
[0075] <Acid resistance stability>
[0076] Acid resistance stability of optical glass (D A ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0077] In some embodiments, the acid resistance stability (DA ) is 2 or more types, preferably 1 type.
[0078] <Weather resistance>
[0079] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:
[0080] Table 1.
[0081]
[0082] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.
[0083] <Bubble Degree>
[0084] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.
[0085] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.
[0086] <Transition Temperature>
[0087] Transition temperature of optical glass (T g ) The test shall be carried out in accordance with the method specified in GB / T7962.16-2010.
[0088] In some embodiments, the transition temperature (T g ) is 700°C or lower, preferably 690°C or lower, and more preferably 685°C or lower.
[0089] <Anti-crystallization properties>
[0090] The test method for anti-crystallization performance is as follows: cut the sample glass into 20×20×10mm specifications and place it in a g Keep the glass in a muffle furnace at +(200-250)℃ for 15-30 minutes, take it out and cool it down, and then observe whether there are crystals or opacity on the surface and inside of the glass. If the glass sample has no opacity and / or crystals, the glass has excellent anti-crystallization performance. This test method is used to characterize the anti-crystallization performance of the secondary pressing glass of the present invention.
[0091] <Striation Degree>
[0092] The striation degree of the glass of the present invention is measured according to the method specified in MLL-G-174B. The method is to use a striation meter composed of a point light source and a lens, and compare and inspect with a standard sample from the direction where the striations are most easily visible. There are 4 levels in total, namely A, B, C, and D. Level A means no striations visible to the naked eye under the specified detection conditions, level B means fine and scattered striations under the specified detection conditions, level C means slight parallel striations under the specified detection conditions, and level D means rough striations under the specified detection conditions.
[0093] In some embodiments, the striae degree of the optical glass of the present invention is C level or higher, preferably B level or higher.
[0094] <High temperature viscosity>
[0095] The high temperature viscosity of optical glass is tested by the following method: The high temperature viscosity of glass is tested using THETA Rheotronic II high temperature viscometer using a rotation method. The unit of value is dPaS (poise). The smaller the value, the lower the viscosity.
[0096] In some embodiments, the viscosity of the optical glass of the present invention at 1400° C. is 45 poise or less, preferably 35 poise or less, and more preferably 1 to 25 poise.
[0097] <Light transmittance>
[0098] Light transmittance of optical glass (τ 400nm ) The test shall be carried out according to the method specified in GB / T 7962.12-2010.
[0099] In some embodiments, the optical glass of the present invention has a light transmittance (τ 400nm ) is 85.0% or more, preferably 87.0% or more, more preferably 88.0% or more, and further preferably 89.0% or more.
[0100] [Method for producing optical glass]
[0101] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1400°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0102] [Glass preforms and optical components]
[0103] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0104] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.
[0105] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0106] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0107] [Optical instruments]
[0108] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.
[0109] Example
[0110] <Optical Glass Example>
[0111] In order to further clearly illustrate and describe the technical solutions of the present invention, the following non-limiting examples are provided.
[0112] This embodiment adopts the manufacturing method of the above optical glass to obtain an optical glass having the composition shown in Table 2 to Table 4. In addition, the characteristics of each glass are measured by the test method described in the present invention, and the measurement results are shown in Table 2 to Table 4. In the anti-crystallization performance test of Table 2 to Table 4, according to the aforementioned test method, the glass without opacity and without crystal particles on the surface and inside is recorded as "A", without opacity and without crystallization particles inside but with crystallization particles on the surface is recorded as "B" (when the glass is pressed twice, the crystallization particles on the surface can be removed by grinding, but the grinding cost will increase, so the glass composition with no crystallization particles inside and outside the glass is more preferred), without opacity but with 1 to 10 crystal particles inside is recorded as "C", without opacity but with 10 to 20 crystal particles inside is recorded as "D", and opacity or dense crystallization particles inside are recorded as "×".
[0113] Table 2.
[0114]
[0115]
[0116] Table 3.
[0117]
[0118]
[0119]
[0120] Table 4.
[0121]
[0122]
[0123] <Glass Preform Example>
[0124] The glass obtained from optical glass examples 1 to 20# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.
[0125] <Optical Element Embodiment>
[0126] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.
[0127] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0128] <Optical Instrument Embodiment>
[0129] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.
Claims
1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 25-35%; ZrO2: 1-8%; BaO: 30-40%; CaO: 1-9%; TiO2: 6-16%; ZnO: 1-9%, wherein (SiO2+ZnO) / (BaO+TiO2) is 0.48-1.
0.
2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: B2O3: 0-9%; and / or Al2O3: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-5%; and / or Li2O: 0-5%; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or WO3: 0-5%; and / or Nb2O5: 0-5%; and / or Ln2O3: 0-10%; and / or clarifier: 0-1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
3. Optical glass, characterized in that: The components include SiO2, ZrO2, BaO, CaO, TiO2 and ZnO, and the components are expressed in weight percentage, wherein (SiO2+ZnO) / (BaO+TiO2) is 0.48-1.0, and the refractive index of the optical glass is n d is 1.69~1.75, Abbe number v d 34.5~40.5, density ρ is 4.00g / cm 3 the following.
4. The optical glass according to claim 3, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 25-35%; and / or ZrO2: 1-8%; and / or BaO: 30-40%; and / or CaO: 1-9%; and / or TiO2: 6-16%; and / or ZnO: 1-9%; and / or B2O3: 0-9%; and / or Al2O3: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-5%; and / or Li2O: 0-5 %; and / or Na2O: 0-5%; and / or K2O: 0-5%; and / or WO3: 0-5%; and / or Nb2O5: 0-5%; and / or Ln2O3: 0-10%; and / or clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
5. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: TiO2 / (CaO+Al2O3) is 0.5-6.0, preferably TiO2 / (CaO+Al2O3) is 0.6-5.0, more preferably TiO2 / (CaO+Al2O3) is 0.8-3.0, and further preferably TiO2 / (CaO+Al2O3) is 1.0-2.0; and / or BaO / (ZrO2+TiO2) is 1.4-5.0, preferably BaO / (ZrO2+TiO2) is 1.5-3.5, more preferably BaO / (ZrO2+TiO2) is 1.6-3.0, and further preferably BaO / (ZrO2+TiO2) is 1.8-2.8; and / or (SiO2+ZnO) / (BaO+TiO2) is 0.5-0.91, preferably (SiO2+ ZnO) / (BaO+TiO2) is 0.6 to 0.9, more preferably (SiO2+ZnO) / (BaO+TiO2) is 0.65 to 0.85; and / or (SiO2+ZrO2) / ZnO is 4.0 to 15.0, preferably (SiO2+ZrO2) / ZnO is 5.0 to 12.0, more preferably (SiO2+ZrO2) / ZnO is 6.0 to 1 0.0, more preferably (SiO2+ZrO2) / ZnO is 6.0~9.5; and / or (TiO2+ZnO) / CaO is 1.0~10.0, preferably (TiO2+ZnO) / CaO is 1.5~8.0, more preferably (TiO2+ZnO) / CaO is 2.0~5.0, and further preferably (TiO2+ZnO) / CaO is 2.5~4.
5.
6. The optical glass according to any one of claims 1 to 4, characterized in that: The components are expressed in weight percentage, wherein: (CaO+SrO) / ZnO is 0.3-5.0, preferably (CaO+SrO) / ZnO is 0.5-3.0, more preferably (CaO+SrO) / ZnO is 0.6-2.0, and further preferably (CaO+SrO) / ZnO is 0.8-1.5; and / or TiO2 / (ZnO+Li2O+SrO) is 0.7 or more, preferably TiO2 / (ZnO+Li2O+SrO) is 0.9-10.0, and more preferably TiO2 / ( The ratio of SiO2 / (BaO+ZnO+Li2O) to SiO2 / (BaO+ZnO+Li2O) is 1.0 to 5.0, and more preferably TiO2 / (ZnO+Li2O+SrO) is 1.5 to 3.5; and / or SiO2 / (BaO+ZnO+Li2O) is 0.5 to 1.0, and preferably SiO2 / (BaO+ZnO+Li2O) is 0.6 to 0.95, and more preferably SiO2 / (BaO+ZnO+Li2O) is 0.65 to 0.95, and more preferably SiO2 / (BaO+ZnO+Li2O) is 0.7 to 0.9 ; and / or (Li2O+Na2O+K2O) / ZrO2 is 0.7 or less, preferably (Li2O+Na2O+K2O) / ZrO2 is 0.5 or less, more preferably (Li2O+Na2O+K2O) / ZrO2 is 0.4 or less, and further preferably (Li2O+Na2O+K2O) / ZrO2 is 0.01 to 0.3; and / or Ln2O3 / TiO2 is 0.4 or less, preferably Ln2O3 / TiO2 is 0.3 or less, and more preferably Ln2O3 / TiO2 is 0.2 or more It is further preferred that Ln2O3 / TiO2 is less than 0.1; and / or (B2O3+Ln2O3) / ZrO2 is less than 5.0, preferably (B2O3+Ln2O3) / ZrO2 is 0.1-3.0, more preferably (B2O3+Ln2O3) / ZrO2 is 0.3-2.0, and further preferably (B2O3+Ln2O3) / ZrO2 is 0.5-1.5, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
7. The optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 27-33%, preferably SiO2: 28-32%; and / or Al2O3: 1-6%, preferably Al2O3: 2-5%; and / or ZrO2: 2-7%, preferably ZrO2: 3-6%; and / or BaO: 32-38%, preferably BaO: 34-37%; and / or CaO: 3-8%, preferably CaO: 4-6%; and / or SrO: 0-2%, preferably SrO: 0-1%; and / or TiO2: 9-15%, preferably TiO2: 10-13%; and / or ZnO: 3-8%, preferably ZnO: 4-6%; and / or Na2O: 0-3%, preferably Na2O: 0-2%; and / or B2O3: 2-7%, preferably B 2O3: 3-6%; and / or MgO: 0-2%, preferably MgO: 0-1%; and / or Li2O: 0-2%, preferably Li2O: 0-1%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%; and / or Ln2O3: 0-5%, preferably Ln2O3: 0-2%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
8. The optical glass according to any one of claims 1 to 4, characterized in that: Its components do not contain MgO; and / or do not contain SrO; and / or do not contain Li2O; and / or do not contain K2O; and / or do not contain WO3; and / or do not contain Nb2O5; and / or do not contain SnO2; and / or do not contain SnO; and / or do not contain CeO2; and / or do not contain As2O3; and / or do not contain PbO; and / or do not contain Ln2O3, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.
9. The optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the optical glass d is 1.69 to 1.75, preferably 1.70 to 1.74, more preferably 1.715 to 1.73, and the Abbe number v d It is 34.5-40.5, preferably 35-40, and more preferably 36-39.
10. The optical glass according to any one of claims 1 to 4, characterized in that: The density of the optical glass is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.80g / cm 3 Below; and / or thermal expansion coefficient α 100 / 300℃ 94×10 -7 / K or less, preferably 92×10 -7 / K or less, more preferably 88×10 -7 / K or less; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A The weather resistance CR is 2 or more, preferably 1; and / or the air bubble degree is A or more, preferably A0 or more, more preferably A 00 level; and / or transition temperature T g is 700°C or less, preferably 690°C or less, more preferably 685°C or less; and / or the striae is C or above, preferably B or above; and / or the viscosity at 1400°C is 45 poise or less, preferably 35 poise or less, more preferably 1 to 25 poise; and / or the light transmittance τ 400nm It is 85.0% or more, preferably 87.0% or more, more preferably 88.0% or more, and further preferably 89.0% or more.
11. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 10.
12. An optical element, characterized in that The optical glass is made of any one of claims 1 to 10, or the glass preform is made of claim 11.
13. An optical instrument, characterized in that Contains the optical glass according to any one of claims 1 to 10, and / or contains the optical element according to claim 12.
Citation Information
Patent Citations
H-ZBaF type optical glass and preparation method thereof
CN107417095A
Optical glass, glass preform, optical component and optical instrument
CN110316961A
Optical glass, optical prefabricated member made of optical glass, optical element and optical instrument
CN110482854A
Optical glass
CN110845139A
Optical glass
US5300467A
